Peran Strategi Pemasaran dalam Optimalisasi Profitabilitas UMKM Makanan dan Minuman di Kota Palembang - Chika Vinolia; Ni Saputri; Rika Lidyah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study aims to analyze the role of marketing strategies in increasing the profitability of food and beverage MSMEs in Palembang City. The approach used is a descriptive qualitative method through in-depth interviews with MSME owners. The results show that digital promotion through social media and marketplaces is the most dominant strategy in driving increased sales, especially among productive-age consumers. Distribution strategies through collaboration with online motorcycle taxi platforms and local retail partners can expand market reach without large operational costs, while product innovation helps maintain competitiveness amidst increasing competition. Overall, the findings of this study confirm that the implementation of appropriate, consistent, and adaptive marketing strategies plays a significant role in optimizing profitability and strengthening the sustainability of food and beverage MSME businesses in Palembang City.